2023
DOI: 10.3389/fpls.2023.1106394
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, photosynthetic light-use efficiency, nitrogen metabolism and nutritional quality of C4 halophyte Portulaca oleracea L. grown indoors under different light intensities and durations

Abstract: Portulaca oleracea L. (known as purslane), is a nutritious facultative C4 halophyte. Recently, it has been successfully grown indoors under LED lightings by our team. However, basic understanding about the impacts of light on purslanes are lacking. This study aimed to investigate the effects of light intensity and duration on productivity, photosynthetic light use efficiency, nitrogen metabolism and nutritional quality of indoor grown purslanes. All plants were grown in 10% artificial seawater hydroponically u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The results of this study revealed a highly complex picture of N metabolism and nutritional quality of purslane grown in different percentages of ASW under different LED spectral qualities as there were no clear trends in their responses to the different treatments. Our recent study with purslane showed that increasing the daily light integral through the optimum combination of light intensity and photoperiod displayed positive effects on the productivity and nutritional quality of purslane [ 73 ]. The influences of LED spectral quality and salinity effects on purslane may also depend on the light intensity or daily light integral, which merit further study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed a highly complex picture of N metabolism and nutritional quality of purslane grown in different percentages of ASW under different LED spectral qualities as there were no clear trends in their responses to the different treatments. Our recent study with purslane showed that increasing the daily light integral through the optimum combination of light intensity and photoperiod displayed positive effects on the productivity and nutritional quality of purslane [ 73 ]. The influences of LED spectral quality and salinity effects on purslane may also depend on the light intensity or daily light integral, which merit further study.…”
Section: Discussionmentioning
confidence: 99%
“…Plants mainly absorb and utilize nitrogen in soil (mainly nitrate nitrogen and ammonium nitrogen) through roots, so the development of roots directly affects plant nitrogen metabolism, and light quality can indirectly regulate plant nitrogen metabolism by affecting root growth [ 37 ]. At the same time, light quality will also directly participate in other aspects of plant nitrogen metabolism, affecting the content of physiological activities related to nitrogen metabolism (nitrate nitrogen, ammonium nitrogen, free amino acid, and soluble protein) and the activities of related nitrogen metabolism enzymes (NR, AS, GOGAT, GS) [ 45 , 46 ]. The results of the present study are that the nitrate nitrogen of XZX24 and HZY261 under the R treatment was higher than those under the B treatment ( Figure 6 A); nevertheless, ammonium nitrogen, free amino acid, and soluble protein of XZX24 and HZY261 under the B treatment were higher than those under the R treatment ( Figure 6 B–D).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble protein: Soluble protein was measured by the Ren [ 46 ] method. Samples (0.1 g fresh rice leaves) were ground up in a mortar with liquid nitrogen, to which 6 mL of a phosphate buffer (pH 7.0) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to purslane plants grown under lower PPFD, shorter photoperiods, and thus lower DLI (240 µmol photon m −2 s −1 , 12 h, DLI = 10.368 mol m −2 day −1 ), higher DLIs (20.736 mol m −2 day −1 ) via different combinations of PPFD and photoperiods promoted root and shoot growth and thus increased shoot productivity. Higher DLIs also enhanced nutritional quality, resulting in higher accumulations of proline and total phenolic compounds as well as dietary minerals such as K, Ca, Mg, and Fe [135]. However, under the same higher DLI (20.736 mol m −2 day −1 ), different combinations of specific PPFD and photoperiod could have different effects on plant growth and the nutritional quality [136].…”
Section: Impacts Of Led Spectral Quality Intensity and Photoperiod On...mentioning
confidence: 99%
“…However, under the same higher DLI (20.736 mol m −2 day −1 ), different combinations of specific PPFD and photoperiod could have different effects on plant growth and the nutritional quality [136]. Overall, growing purslane under a PPFD of 320 µmol m −2 s −1 with 18 h photoperiod (DLI = 20.736 mol m −2 day −1 ) is the most suitable strategy for enhancing the productivity and nutritional quality of purslane [135]. However, purslane grown under the CL condition with the same DLI (240 µmol photon m −2 s −1 , 24 h photoperiod) had lower shoot and root biomass, which resulted from the lower maximal quantum efficiency of PS II (F v /F m ratios < 0.8) and lower electron transport rate, indicating photoinhibition and low light use efficiency [137].…”
Section: Impacts Of Led Spectral Quality Intensity and Photoperiod On...mentioning
confidence: 99%